Understanding Corporate Values: how Sainsbury's values make them different - Johnson, Daniel (2012)
This three company comparative study aims to develop understanding of Corporate Values by investing Sainsbury’s claim that “Our Values Make Us Different”. The three companies selected for this study are Sainsbury’s, Tesco, and Morrisons, who are all direct competitors in the UK Groceries market, accounting for 60% of the market share by till receipts. In order to assess this claim, broad understanding of the value concept is applied from other social science disciplines, predominantly psychology. It is subsequently noted that the majority of the literature surrounding corporate values is descriptive in nature. Therefore a new definition of the value concept is offered: a value is an individually held, foundational belief which; inspires preferable behaviour, or indicates a preferable end-state of existence worth striving for. It is believed that this definition is able to provide a greater depth of understanding into values, in general, as well as their application to corporations. This research is stimulated off the back of the rise of awareness, and importance attached to values, in society in general, and is applying a depth of understanding to a much discussed, yet little understood phenomenon. It is therefore also observed that the majority of writing around the subject of value is in publications such as practitioner magazines, rather than academic journals and text books. The introductory chapter takes a look at why values are becoming so important in society, by tracking the role of the corporation in society through history, and concluding that economic and social development achieved since World War 2 has permitted the growth of post-material values in society, concern with issues like social welfare and the environment, which businesses are also being forced to adopt. The literature review provides an overview of much of the current thought around the subject area of values in general, and especially in the context of corporate values, and justification and explanation of why a new definition was created, is given. The methodology chapter provides the reader with the underlying assumptions of the author, and details how the companies were selected, and the data analysed. The analysis of the findings chapter, attempts to answer the research question of How do Sainsbury’s values make them different? And all the information is brought back together in the summary and conclusions section, where also some of the limitations of the project are considered, and some future potential research directions are explored